Assessing the performance of SN-SPI and SPI and the trend assessment of drought using the XI correlation technique over Iran. Issue 8 (9th August 2022) - Ghasemi, Mohammad Mehdi; Mokarram, Marzieh; Zarei, Abdol Rassoul
Abstract: In recent decades, human activities such as the excessive production of carbon dioxide gas, deforestation, overexploitation of natural resources, and so on have caused changes in the climate regimes and frequent occurrence of droughts. Thus, the investigation of the trend of changes in drought can be effective in better understanding the drought condition and also more properly managing the adverse effects of drought. Therefore, in this study, the trend of changes in drought was assessed based on the standardized precipitation index (SPI) and the spatially normalized SPI (SN-SPI) in 34 stations over Iran on 1-, 3-, 6-, and 12-month time scales from 1967 to 2019 using the XI correlation technique (XICOR). Then, using the mean residual error (MRE) index and also a comparison of the correlation coefficient (CC) between the SPI and SN-SPI values with a perfect reliable line (line with the equation Y = X - or T -Statistics index), the performances of the SPI and SN-SPI were investigated. The results of the trend assessment indicated that the SPI and SN-SPI had almost the same performance in all chosen time scales (including 1-, 3-, 6-, and 12-month). However, the results of the T - Statistics and MRE revealed that the calculated values of the SN-SPI in more than 80% of the chosen stations (in the selected time scales) were different from the SPI, and in more than 70% of stations, the calculated values of the SN-SPI were less than the SPI. Therefore, it can be said that the SN-SPI has a different performance from the SPI, and under the influence of spatial normalization of the precipitation values in the SN-SPI, the overall level of the calculated SN-SPI values will be decreased. HIGHLIGHTS: The XICOR as a new method was used to assess the trend of change. The SN-SPI and the SPI were used to estimate drought conditions. In this research, data series of 34 stations with various climate conditions were used. In this research, the performance of the SN-SPI and SPI was compared. Graphical Abstract